A review on damping of torsional interactions using VSC based FACTS and subsynchronous damping controller. (2018) - Venkateswarlu, S.; Janaki, M.; Thirumalaivasan, R.; Prabhu, Nagesh
Abstract: Improvement in the power transfer capability and the system stability of long transmission lines by series compensation is a cost-effective solution. However, the Subsynchronous Resonance (SSR) due to series compensation leads to severe risk of Torsional Interactions (TI). This paper presents, a review on damping of torsional interactions using Voltage Source Converter (VSC) based FACTS with various Subsynchronous Damping Controllers (SSDC) proposed in the literature. This review can help researchers to make a comparative study of the impact of FACTS devices and various subsynchronous damping controllers on damping of subsynchronous oscillations.